Victorian Studies, Literature, and the Global Nineteenth Century. Issue 1 (1st June 2022) - Valdez, Jessica R.
Abstract : This essay advocates critical examination of the function of the 'global' in global nineteenth-century studies. Using the Victorian novel as a case study, this essay conceives global nineteenth-century studies as a site for disciplinary boundary crossing, in which scholars across fields can dialogue to expand their historical, geographical, and methodological scope, while still respecting field-specific expertise and localized historical knowledge.